Overcoming immune evasion with innovative multi-target approaches for glioblastoma - Su, Hai; Peng, Yin; Wu, Yilong; Zeng, Xiaoli (Frontiers in Immunology, 2025)
Glioblastoma (GBM) cells leverage complex endogenous and environmental regulatory mechanisms to drive proliferation, invasion, and metastasis. Tumor immune evasion, facilitated by a multifactorial network, poses a significant challenge to effective therapy, as evidenced by the limited clinical benefits of monotherapies, highlighting the adaptive nature of immune evasion. This review explores glioblastoma’s immune evasion mechanisms, the role of ICIs in the tumor microenvironment, and recent clinical advancements, offering theoretical insights and directions for monotherapy and combination therapy in glioblastoma management.